BIZARRE FOSSIL INSECTS: WEB-SPINNING SAWFLIES OF THE GENUS FERGANOLYDA (VESPIDA, PAMPHILIOIDEA) FROM THE MIDDLE JURASSIC OF DAOHUGOU, INNER MONGOLIA, CHINA - Rasnitsyn A.P.; Zhang H.; Wang B. (My University, 2006)
Three new species, attributed to the extinct family Xyelydidae of the Pamphilioidea (Order Vespida = Hymenoptera), are described from the Middle Jurassic of Daohugou, Inner Mongolia, China: Ferganolyda scylla sp. nov., F. charybdis sp. nov. and F. chungkuei sp. nov. The new material demonstrates that the genus Ferganolyda, which was previously considered to be a morphologically ordinary group of web-spinning sawflies, is in fact a highly unusual insect taxon. It is characterised, particularly in the male sex, by a huge head (about half as wide as the entire body length) and unusual modification of the antennae. Interpretation of the function of the unusual head and antennae is intriguing but unresolved. © 2006 The Palaeontological Association.
Keywords: CHINA; DAOHUGOU; MIDDLE JURASSIC; VESPIDA; WEB-SPINNING SAWFLIES; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская